Knowledge, attitudes and practice towards yellow fever among nomadic populations: A cross-sectional study in yellow fever outbreak communities in Ghana. - Abdul-Wahab Inusah; Gbeti Collins; Peter Dzomeku; Michael Head; Shamsu-Deen Ziblim (Public Library of Science (PLoS), 2023)
Despite the government and global health initiatives toward yellow fever epidemic control in Ghana, the country continues to witness sporadic outbreaks of yellow fever mostly among the unvaccinated population and suspected migrates(nomadic) who enter the country. Little is known about nomadic knowledge, attitudes and practice regarding this communicable disease in Ghana. We conducted a community-based cross-sectional survey in 22 yellow fever outbreak communities to assess nomadic household heads' knowledge, attitudes and practices (KAP) regarding yellow fever after an outbreak in November 2021 outbreak. Our study results were analyzed using descriptive statistics, bivariate and multivariate logistics regression with dichotomous outcomes. Significant statistics were obtained from multivariate analysis. About 90% of the nomadic had poor knowledge of the signs and symptoms of yellow with only 16% knowing the vector that transmits yellow fever. The most common source of information on yellow fever was the health campaign. Over 80% of household heads surveyed had positive attitudes regarding yellow fever with about 84% worried about the disease outbreak in their community. In a multivariate logistic regression model, age group(AOR = 2.79; 95% CI: 1.31, 5.98, p = 0.008)., gender ideology(AOR = 2.27; 95% CI: 1.14-4.51, p = 0.019), occupation(AOR = 15.65; 95% CI: 7.02, 34.87, p<0.001), source of health information(AOR = 0.27; 95% CI: 0.07, 0.96, p = 0.043), duration of stay in the community(AOR = 1.11; 95% CI: 1.31, 5.98, p = 0.008) and nationality (AOR = 0.22; 95% CI:0.47, 0.47, p<0.001) were associated with positive attitudes towards yellow fever. Close to 74% have a positive practice, with 97.3% controlling mosquitoes in their household. Nationality (AOR = 3.85; 95% CI: 2.26, 6.56, p<0.001), duration of stay in the community (AOR = 1.06; 95% CI: 1.03, 1.10, p = 0.001), and age group(AOR = 040; 95% CI: 0.22, 0.73, p = 0.003) were associated with positive practices. Our findings show that yellow fever KAP was variable with clear knowledge gaps. Regular locally-tailored education and health promotion campaigns should be considered to improve knowledge and preventive practices against this infectious disease.